Mechanical properties and stability of precipitates of an ODS steel after thermal cycling and aging. (August 2020) - Oñoro, M.; Macías-Delgado, J.; Auger, M.A.; de Castro, V.; Leguey, T.
Highlights: No changes in mechanical strength after thermal cycling or aging. High stability of Ti-rich oxides. Chemical evolution and redistribution of Cr-W-rich precipitates along grain boundaries. Loss of ductility after thermal aging attributed to grain boundary embrittlement. Abstract: The thermal stability of an ODS RAF steel has been investigated by assessing the effects of different thermal treatments on its microstructure and mechanical behavior. The ODS steel, with nominal composition Fe–14Cr–2W–0.4Ti-0.3Y2 O3 (wt. %), was manufactured by mechanical alloying, compacted by hot isostatic pressing and hot cross rolling. Following the rolling process, short thermal treatments at temperatures between 1073 and 1473 K were applied, and an optimal annealing temperature of 1273 K was selected. Afterwards, two independent thermal treatments were applied. To check the effects of thermal fatigue, a set of samples was submitted to thermal cycling between 773 and 1073 K. Finally, another batch was thermally aged at 873 K for 2000 h. A Vickers microhardness analysis shows a hardening effect with the thermal cycling and the aging treatments. The cycling treatment causes a small improvement of yield and tensile strengths at test temperatures T > 773 K, without clear ductility changes. The aging treatment slightly enhances tensile properties for tests at T > 873 K, together with loss of strength and ductility in tests at T < 873 K. Microstructural investigations show no changes in the grain structure. However, the oxide and Cr-W-rich secondary phases studied in this work present different behaviors. Ti-rich oxides appear quite stable, without significant variations in their location, composition, morphology, and size distribution. With respect to the existing Cr-W-rich precipitates, the aging treatment promoted their redistribution and diffusion along grain boundaries, together with compositional changes, which would account for the slight strengthening and loss of ductility observed.